The use of a low-flux hemo-dialyzer is associated with impaired platelet aggregation in patients undergoing chronic hemodialysis. Issue 43 (28th October 2022) - Chen, Ching-Yang; Liou, Hung-Hsiang; Chang, Min-Yu; Wang, Hsi-Hao; Lee, Yi-Che; Ho, Li-Chun; Lin, Tsun-Mei; Hung, Shih-Yuan
Abstract : In patients with chronic hemodialysis (HD), both abnormal thrombotic and bleeding events are commonly observed. Uremic platelet dysfunction is one of the important attributing factors. Moreover, HD may also result in aggregation dysfunction of platelets during the therapeutic procedure. However, how the HD process affects platelet and coagulation function is unknown and dialyzer membrane flux could have an impact on it. We aimed to compare the impacts of low-flux and high-flux HD on the platelet function of patients undergoing chronic HD. This was a cross-sectional study conducted in the HD unit of E-Da hospital in Taiwan. A total of 78 patients with maintenance HD three times per week for more than one year, including 40 with high- and 38 with low-flux hemodialysis, were recruited. Their platelet functions were evaluated using an in vitro platelet function analyzer (PFA-100) before and after the HD session. Of the 78 patients undergoing HD, 60 (76%) had prolonged pre-dialysis collagen/epinephrine (CEPI) and collagen/adenosine diphosphate closure times. Those receiving low-flux dialyzer had a significant increase in CEPI closure time (pre-dialysis 212.3 ± 62.1 seconds. post-dialysis 241.5 ± 64.3 seconds, P  = .01), but not collagen/adenosine diphosphate closure time, after HD. After adjusting confounding factors, only the low-flux dialyzer demonstrated an independent association with the prolonged CEPI closure time after HD therapy (odds ratio = 23.31, 95% CI: 1.94–280.61, P  = .01). We observed that impaired platelet aggregation is prevalent in patients undergoing chronic HD. Therefore, the use of low-flux dialyzers may further worsen platelet aggregation after dialysis. Patients with uremic bleeding diathesis should take precautions. We suggest that further studies using flow cytometry should be conducted to explore the mechanism of dialysis flux and platelet activity during HD.